Intranasal Dexmedetomidine vs. Oral Midazolam in Pediatric Emergence Agitation Management Following Anesthesia; A Double Blind Randomized Clinical Trial - Nastaran Sadat Mahdavi; Fatemeh Jafari; Farnaz Shahabi Shojaei; Seyed Sajjad Razavi; Mortazavi, Morteza; Ali Reza Mahdavi (Archives of Academic Emergency Medicine, 2025)
Introduction: Emergence agitation (EA) occurs shortly after emergence from anesthesia in pediatric patients causing disorientation, restlessness, and non-purposeful movement. This study aimed to compare intranasal dexmedetomidine (DEX) and oral midazolam in managing EA in pediatric patients scheduled for neurosurgical procedures. Methods: This double-blinded randomized clinical trial was conducted on 50 pediatric patients who underwent neurosurgical procedure in an educational hospital between March and June 2024. One group received intranasal DEX (2 mcg/kg) and other group received oral midazolam (1 mg/kg of midazolam) before induction of anesthesia. The rate of EA as well as vital signs changes were compared between the two groups using statistical analysis. Results: 50 participants were enrolled in the study and randomly divided to DEX and midazolam groups (25 participants in each group). The two groups were similar regarding age (p = 0.538); sex (p = 0.417); pre-operation heart rate (p = 0.675); systolic (p = 0.226) and diastolic (p = 0.753) blood pressure; and pre-operative mean arterial blood pressure (p = 0.634). Among all participants, 13 (26.00%) patients showed signs of EA after extubation (2 patients (8.00%) in DEX group and 11 (44.00%) patients in midazolam group; p = 0.004). Regrading vital signs, only the decrease in heart rate after extubation in the DEX group was significantly greater than that observed in the midazolam group (-9.28±12.88 vs. -2.48±8.23, respectively; p = 0.0310). The number needed to treat (NNT), relative risk reduction (RRR), and absolute risk reduction (ARR) of using intranasal DEX in management of EA were 2.77 (95%confidence interval (CI): 1.72-7.19), 81.8% (95%CI: 26.0%-95.5%), and 36.0% (95%CI: 13.9%-58.1%) respectively. Conclusion: Intranasal DEX compare to oral midazolam demonstrated superior efficacy in managing postoperative EA in pediatric patients.